Improved self‐perceived performance for continence problems in patients with Parkinson's disease after deep brain stimulation. Issue 2 (22nd November 2018) - Nakamura, Kumiko; Yamanaka, Yoshitaka; Higuchi, Yoshinori; Hirano, Shigeki; Kuroiwa, Ryota; Abe, Midori; Murata, Astushi; Iwadate, Yasuo; Kuwabara, Satoshi; Yamamoto, Tatsuya
Abstract: Background: Deep brain stimulation (DBS) is known to improve motor complications in patients with Parkinson's disease (PD); however, we lack information on how it changes self‐perceived performance for activities of daily living. Aim: We assessed the degree of change in self‐perceived performance for activities of daily living after DBS. Method: We applied the Canadian Occupational Performance Measure (COPM) in 21 patients with PD who underwent DBS before and 1 year after surgery and examined the relationship among the COPM score, motor and cognitive functions, and health‐related quality of life (HRQoL). Results: Patients prioritized continence problems, gait, and household work. Self‐perceived performance satisfaction (5.46→8.38, P = 0.02) and execution (5.85→8.88, P = 0.01) for continence problems improved significantly after surgery. Self‐perceived performance satisfaction for gait tended to improve after surgery. Self‐perceived performance for household work did not change after surgery. Self‐perceived performance for continence problems negatively correlated with PD questionnaire (PDQ‐39; r = −0.827, P = 0.007) before surgery and Mini‐Mental State Examination (MMSE; r = −0.918, P = 0.028) after surgery. Conclusion: The self‐perceived performance for continence problems improved significantly after DBS and was associated with HRQoL before surgery and MMSE after surgery.